Proposta do framework visão periférica estendida para a geração de ideias e inovações em empresas de serviços de tecnologia da informação a partir de sinais externos - Malachias, Celso dos Santos (2016)
This dissertation examines the mechanisms companies use to acquire and interpret market signals, and which stimulate innovation. It applies the Extended Peripheral Vision (EPV) conceptual framework, which represents a company’s capacity to monitor its external environment, acquire information, and convert it into ideas and innovation. As a proposition, it argues that the elements that compose the EPV framework impact on the generation of ideas and on the implementation of innovation. Following a qualitative methodology, interviews with top-level executives from twelve Information Technology service companies were conducted. This study found evidences that support the proposed EPV framework as a mechanism of idea and innovation generation from external signals. The company that generated more innovations was also the one most adherent to the framework. The external validity of the model was made by comparing this research results with secondary data from publicly available reports on innovation, prepared by consulting firms. The interviews with the top-level executives confirmed the proposed stages in the framework. These can be aggregated into three groups: 1) capabilities, 2) practices, and 3) trends. 1) The capabilities could be further divided into leadership, behavioral, market-related, reframing, “glocal”, and associated to engineering. 2) The practices seen as relevant for the production of ideas and innovation can be categorized in: search of standards, procedures, expansion of the client’s scope of analyzes, and market analysis. 3) The trends companies have monitored are: technology, business models and socio-demographic trends. The resulting innovations were related to: process, product, business model, organizational, structural, and marketing. This dissertation contributes to the business management practice with a conceptual framework for the generation of ideas and innovation, based on external signals to the company. Moreover, it presents a series of practices and capabilities that business leaders can use and replicate in their own context. It also contributes to the academic scholars with an updated literature review of the innovation topic coming from external signals, in an integrated form of its constitutive elements.